The empire strikes back: options and reform decisions - Christiansen, Peter Munk; Klitgaard, Michael Baggesen (Politica, 2020)
Political decision making based on institutionalized coordination between the state and relevant societal interests facilitated consensus and generated stable political solutions in the era of class politics. Beyond class politics and in the era of permanent austerity, governments are often caught in situations in which they pursue reform intentions that necessitate infliction of concentrated losses on organized interests, which reduce the possibility to achieve consensus. We argue that partisan governments in the post-class politics terrain rather than experiencing reduced reform capacities have more room for maneuvering and more flexibility in formation of viable reform alliances with organized interest groups. In effect, governments have improved strategic opportunities to maximize a partisan imprint on policy. The price they pay, however, is reduced consensus and reduced political stability around the decisions and policies that are carried through. We illustrate the relevance of this theoretical argument in case studies of three significant policy decisions in Denmark: a) (parts of) the local government reform from 2007, b) the decision to regulate public school teachers working conditions by law from 2013, c) the reduction of the inheritance taxes imposed on family-owned companies from 2017. In all three cases, the government implemented reforms in strategic alliances with some interest groups against the preferences of others and broke with traditional allies in the interest group terrain. In all three cases, the government maximized policy influence and had to accept that the policy decisions remain contested by alternative coalitions and majorities.